2023
DOI: 10.1002/aenm.202204353
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Polymeric Phthalocyanine‐Coated Carbon Nanotubes for Efficient Redox Mediators of Lithium–Sulfur Batteries

Abstract: than conventional lithium-ion (Li-ion) batteries. [1] However, the inherent limitations of currently available LiS batteries-namely their volume expansion during the charge-discharge process, the shuttle effect of lithium polysulfides (LiPSs), and the low intrinsic conductivity of S-hamper their commercialization. [2] Extensive research is needed to develop affordable S host materials that can resolve the above-mentioned limitations, as this will enable the development of practical LiS batteries with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…21 While the incorporation of NiPc inhibits the growth of P−O−C bonds, which may be related to the structure of MPc with a highly catalytically active site M-N 4 . As shown in Figure 1f N 1s XPS spectra, 16 The micromorphology and structure of samples were analyzed by scanning electron microscope (SEM) (Figure S2a−d). The test results show that MPc@RP/C and RP/C present a few microns in size and irregular lumpy particles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…21 While the incorporation of NiPc inhibits the growth of P−O−C bonds, which may be related to the structure of MPc with a highly catalytically active site M-N 4 . As shown in Figure 1f N 1s XPS spectra, 16 The micromorphology and structure of samples were analyzed by scanning electron microscope (SEM) (Figure S2a−d). The test results show that MPc@RP/C and RP/C present a few microns in size and irregular lumpy particles.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Lee and co-workers designed a multifunctional polymeric cobalt phthalocyanine molecule with triethylene glycol linkers (TCP) and loaded it onto carbon nanotubes to obtain TCP/MCs. 16 Electrochemical and theoretical analyses verified that cobalt ions in the phthalocyanine center can provide redox mediating capacity, which facilitates the kinetics of polysulfide uptake and conversion reactions. Additionally, the nitrogen atom displays a strong polar interaction with Li, resulting in a lithophilic effect.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, traditional MOFs usually also suffer from poor electronic conductivity, which impedes the full exploitation of their electrochemical performances, particularly the high-rate performance. Recent studies demonstrated that MOF-derived electrode materials with enhanced electronic conductivity could promise significant applied implications for energy storage applications. However, to achieve the direct use of the prepared MOF materials as active materials for KIB anodes, it is critical to endow the designed MOFs with the combination of superior redox activity, outstanding stability, and high conductivity.…”
Section: Introductionmentioning
confidence: 99%